Adoption of accounting mobile apps in Kenya: The effect of user reviews and user ratings - Kamau, Charles, Guandaru; Asser, Juliana, Hawario; Otiende, Isaac, Ojung'a (My University, 2023)
Modern industry improves anthropogenic activities and greatly simplifies human effort and the industrial world. Cloud computing and mobile applications are more than just buzzwords; they are crucial elements of how business is conducted and how it will be conducted in the future. A rising number of SMEs are currently utilizing mobile and cloud computing technology. The purpose of this paper is to analyze the linkages between user reviews and ratings and the adoption of mobile accounting apps among SMEs in Kenya. The study collected data on 35 commonly used mobile accounting applications and performed a regression analysis on 27 apps that had received user reviews. Data on mobile apps' usage rate, volume of user reviews, and user ratings were gathered for this study. The authors also took note of the deficiencies identified by the selected mobile app reviewers. This study's findings revealed a significant relationship between the number of user evaluations and the adoption of mobile accounting apps. However, a significant effect of user reviews on the adoption of mobile accounting apps was not observed. This paper also identifies shortcomings that app users have pointed out in their reviews. It was concluded that Kenya's degree of mobile app adoption has greatly increased due to the volume of app reviews. This study advises entrepreneurs, particularly those who engage with SMEs, to embrace technology and adopt freely downloadable mobile apps for their accounting and bookkeeping requirements.
Keywords: Accounting Mobile Apps; Kenyan SMEs; User Rating; User Reviews